K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 2 2021

1) Ta có a2 + b2 + c2 = ab + bc + ca

=> 2a2 + 2b2 + 2c2 = 2ab + 2bc + 2ca

=> 2a2 + 2b2 + 2c2 - 2ab - 2bc - 2ca = 0

=> (a2 - 2ab + b2) + (b2 - 2bc + c2) + (a2 - 2ac + c2) = 0

=> (a - b)2 + (b - c)2 + (a - c)2 = 0

=> \(\hept{\begin{cases}a-b=0\\b-c=0\\a-c=0\end{cases}}\Rightarrow\hept{\begin{cases}a=b\\b=c\\a=c\end{cases}}\Rightarrow a=b=c\left(\text{đpcm}\right)\)

16 tháng 2 2021

a^2 + b^2 + c^2 = ab + bc + ca

<=> 2a^2 + 2b^2 + 2c^2 - 2ab - 2ac - 2bc = 0

<=> (a-b)^2 + (b-c)^2 + (c-a)^2 = 0

<=> a-b = 0 và b-c=0 và c-a=0

<=> a=b=c

a^2/b+c + b^2/a+c + c^2=a+b

= a(a/b+c) + b(b/a+c) + c(c/a+b)

= a(a/b+c + 1 - 1) + b(b/a+c + 1 - 1) + c(c/a+b + 1 - 1)

= a(a+b+c/b+c) - a + b(a+b+c/a+c) - b + c(a+b+c/a+b) - c

= (a+b+c)(a/b+c + b/a+c + c/a+b) - (A+b+c)

mà a/b+c + b/a+c + c/a+b = 1

= a+b+c - (a+b+c)

= 0

14 tháng 7 2019

1.từ bt trên ta có thể suy ra

=a^2+c^2+b^2+2ab+2ac+2bc+a^2+b^2+c^2

=(a+b)^2+(b+c)^2+(a+c)^2

30 tháng 9 2018

Câu 4 : 

       Ta có : a+b+c=0

​​=> a+b=-c

Lại có : a3+b3=(a+b)3-3ab(a+b)

=> a3+b3+c3=(a+b)3-3ab(a+b)+c3

                    =-c3-3ab. (-c)+c3

                    =3abc

Vậy a3+b3+c3=3abc với a+b+c=0